2019
DOI: 10.3390/ani9110872
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Resveratrol Improves Systemic Inflammation Responses in LPS-Injected Lambs

Abstract: Simple SummaryChina’s livestock industry has been transforming from traditional extensive systems to highly intensive systems. Highly intensive livestock production often causes immune stress to animals, which makes them more susceptible to infections. The aim of this study was to examine whether resveratrol alleviates inflammation in lambs. Results showed that resveratrol attenuated the LPS-evoked inflammatory responses in lambs by suppressing expression levels of inflammatory cytokines and blocking NF-κB and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 46 publications
(58 reference statements)
1
20
0
Order By: Relevance
“…Previous studies have shown that supplementation with RES can reduce the level of ACTH and beneficially protect broilers against heat stress (Zhang et al 2017;He et al 2019). Liang et al (2019) demonstrated that RES inhibited the production and secretion of cortisol in LPS challenged lambs. Studies in rodents also illustrated that RES alleviated heat stress by decreasing serum cortisol level (Cheng et al 2019), which suggests that RES was not species specific in its functions and could be most likely to be applied to all animals.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies have shown that supplementation with RES can reduce the level of ACTH and beneficially protect broilers against heat stress (Zhang et al 2017;He et al 2019). Liang et al (2019) demonstrated that RES inhibited the production and secretion of cortisol in LPS challenged lambs. Studies in rodents also illustrated that RES alleviated heat stress by decreasing serum cortisol level (Cheng et al 2019), which suggests that RES was not species specific in its functions and could be most likely to be applied to all animals.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, IL-4 is thought to suppress or decrease the inflammatory responses by inhibiting the secretion of pro-inflammatory cytokines, such as IL-1b, IL-6, and TNF-a (Rubinstein and Rubinstein 1990). Previous studies have demonstrated that RES supplementation, under stress conditions, displays beneficial activity against inflammatory responses in piglets (Gan et al 2019), rats (Cheng et al 2019) and lambs (Liang et al 2019) by modulating the production of cytokines. In the present study, injecting diquat significantly increased the levels of serum IL-1b, IL-6, and TNF-a, whereas decreased the levels of serum IL-4 in piglets.…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol prevents ventricular hypertrophy (Chelladurai et al, 2019) and cardiac remodeling following chronic kidney disease (Li et al, 2020a). Resveratrol also helps to protect aortic valve stenosis (Samiei et al, 2019), septic cardiomyopathy (Liang et al, 2019), diabetic cardiomyopathy (Hoseini et al, 2019), and heart failure (Algieri et al, 2019). Most associated studies have focused on the influence of resveratrol on hyperlipemia-related cardiomyocyte damage or metabolic reprogramming, but not on high-fat-related endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that polyphenols can modulate the immune functions through binding to cellular receptors and altering the cell pathways, thereby regulating the host immune response ( 153 ). For instance, curcumin and resveratrol have been evidenced to inhibit the signaling pathway of nuclear factor-kappa β (NF-κβ) and thereby inhibit the release of the proinflammatory cytokine TNF-α ( 154 ). Curcumin has been reported to have a role in activation and proliferation of B and T lymphocytes, increase the antibody titer against some viruses, enhance innate immunity in challenged animals, improve the immune response by increasing leucocyte count and phagocytic activates, and stimulate the function of plasma lysozyme and increased immunoglobulin ( 146 , 155 , 156 ).…”
Section: Phytogenic Feed Additivesmentioning
confidence: 99%